Child with hypocalcaemia: a rare case of HDR syndrome - George, Jewel Maria; Cherian, Carol Sara; Philip, Rajeev; Sunnychan, Sebin (International Journal of Contemporary Pediatrics, 2025)
Barakat syndrome (also known as HDR syndrome) is an autosomal dominant disorder characterized by the triad of Hypoparathyroidism (H), nerve Deafness (D) and/or renal disease caused by mutation of the GATA3 gene located at chromosome 10p15. This syndrome is very rare with exact prevalence not known and only few cases are reported in the literature. 4-month-old baby girl, diagnosed as hypoparathyroidism on supplements, presented with seizures due to hypocalcemia. On detailed evaluation, child was found to have bilateral hearing loss. Facial dysmorphisms were noted in the form of bulbous nose with everted nares, long philtrum, thin upper lip, low set ears and bilateral non paralytic convergent squint. External genitalia showed perianal groove with an anteriorly placed anus. Startle response was blunted. Other systemic examination was within normal limits. Routine blood investigations revealed low serum calcium (calcium (total) 4.8 mg/dl) and high serum phosphorous level (11.3 mg/dl). Serum parathormone level was 4.4pg/ml and vitamin D levels were insufficient. Child was managed with IV calcium correction and 1,25 (OH)2 VIT D3. The brainstem evoked response audiometry (BERA) showed severe hearing loss. Next - generation sequencing showed a heterozygous missense variant in exon 4 of the GATA 3 gene which was suggestive of Hypoparathyroidism, sensorineural deafness, and renal dysplasia syndrome. This case report aims to provide awareness of rare inherited conditions in a patient with abnormal physical and laboratory findings even though their initial presentation was seizure and hypocalcemia.